Living Quixote : performative activism in contemporary Brazil and the Americas - Miñana, Rogelio, 1972- (Performing Latin American and Caribbean identities., 2020)
"Examines contemporary appropriations of Miguel de Cervantes's masterpiece in political and social justice movements in the Americas, particularly in Brazil. The author examines long-term, Quixote-inspired activist efforts at the ground level, offering an applied model for cultural activism or, as he calls it, performative activism"--